Delay in diagnosis and treatment among adult multidrug resistant tuberculosis patients in Yangon Regional Tuberculosis Center, Myanmar: a cross-sectional study - Ye Minn Htun; Tin Mi Mi Khaing; Yin Yin; Zaw Myint; Si Thu Aung; Tin Maung Hlaing; Ngamphol Soonthornworasiri; Udomsak Silachamroon; Yuthichai Kasetjaroen; Jaranit Kaewkungwal (BMC, 2018)
Abstract Background Delays in diagnosis and treatment initiation may allow the emergence of new cases by transmission to the community, and is one of the challenges facing programme management of drug resistance in Myanmar. This study aimed to explore delays in diagnosis and treatment initiation, and associated factors among patients with multidrug-resistant tuberculosis. Methods A cross-sectional study was conducted at Yangon Regional Tuberculosis Centre, Myanmar. Data were collected by face-to-face interviews and treatment-card reviews of all adult patients who had registered and started treatment with the standard regimen from May to November, 2017. Delay time was categorized by using median cut-off and analyzed using SPSS version 23.0. Logistic regression analysis was performed to assess the relative impact of predictor variables on diagnosis and treatment delays. Results A total of 210 patients participated in this study. The median diagnosis delay was 9 days, IQR 3 (8-11) and 58.6% of the patients experienced a long diagnosis delay. Below middle school education (adjusted odds ratio [AOR] = 2.75, 95% CI = 1.22-6.21), non-permanent salaried employment (AOR = 3.03, 95% CI = 1.32-6.95), co-existing diabetes mellitus (AOR = 5.06, 95% CI = 1.97-13.01) and poor awareness (AOR = 2.99, 95% CI = 1.29-6.92) were independent predictors of long diagnosis delay. The median treatment delay was 13 days, IQR 9 (8-17) and 51% of the patients experienced long treatment delay. Age 31-50 years (AOR = 4.50, 95% CI = 1.47-13.97) and age > 50 years (AOR = 9.40, 95% CI = 2.55-34.83), history with MDR-TB patient (AOR = 3.16, 95% CI = 1.29-7.69), > 20 km away from a Regional TB Centre (AOR = 14.33, 95% CI = 1.91-107.64) and poor awareness (AOR = 4.62, 95% CI = 1.56-13.67) were independent predictors of long treatment delay. Conclusions Strengthening comprehensive health education, enhancing treatment adherence counseling, providing more Xpert MTB/RIF machines, expanding decentralized MDR-TB treatment centers, ensuring timely sputum transportation, provision of a patient support package immediately after confirmation, and strengthening contact-tracing for all household contacts with MDR-TB patients and active tuberculosis screening were the most effective ways to shorten delays in MDR-TB diagnosis and treatment initiation.